A Study in Population Growth and Characteristics of Patna Urban Agglomeration - Kumar, Anjani; Yadava, R. S. (National Geographical Journal of India, 2022)
The study of population growth and demographic characteristics of a city in the spatio-temporal framework provide scope to understand evolutionary processes of an urban settlement. The present work has examined the urban agglomeration, in geographic perspective, which constitutes a significant component of Indian urban scenario. In comparison to the global urban scenario, India's lower urbanisation contains arelatively large proportion of the urban population in its metropolises and urban agglomerations. Patna, the capital of Bihar, has witnessed multiple political, economic, social and religious movements for several centuries which gradually resulted ina diverse pattern of growth and a complex demographic structure. The city has grown linearly along the southern bank of river Ganga, but under the influence of recent global urbanisation trend, past few decades, it is experiencing the growth in a haphazard manner. The study uses the secondary sources of data.Census of India data from different decades viz. 1971, 1981, 1991, 2001 and 2011 has been used to examine the sequential change in population growth and demographic characteristics. Attempts are made to analyse the correlation between literacy and sex ratio as well as literacy and working population since these are the prominent indicators of urban and social development. Spearman rank difference method has been used to get the coefficient of correlation. Final administrative map down to ward level has been prepared using raw maps made available by different authorities and government reports. The thematic maps have been prepared using census data.The present work is an endeavour to understand impact and causes of sequential population growth and demographic characteristics of Patna urban agglomeration using descriptive as well as geoinformatics approach of study.